(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
Chloroquine has gained great emphasis in the treatment of malaria. This study sought experimentally to determine the histomorphological and weight changes in the testes of male mice infected with Plasmodium berghei and treated with chloroquine. The study used 30 Swiss mice divided into five groups. Group 1 is Control that was not infected with Plasmodium berghei and not treated with chloroquine as control, Group 2 is Plasmodium (Plasmodiul berghei) Infected animals but not treated, Group 3 is Plasmodium Infected animals + Chloroquine (5mg/kg), Group 4 is Plasmodium Infected animals + Chloroquine (10mg/kg) and Group 5 is Plasmodium Infected animals + Chloroquine (15mg/kg). The mice were treated for 7 days after parasitaemia was confirmed and the Group 2-5 testes studied with reference to Group 1. The results showed that the Group 2 showed a little distortion, difference in spermatogenic activities and increased cellular activities; Group 3 showed large, convoluted tubules, moderate number of spermatids and large interstitial spaces, Group 4 showed Large seminiferous tubules, large spermatids, increased distortion and group 5 showed shrinking of seminiferous tubules, degeneration of interstitial cells of Leydig cells and Sertolic cells with spermatids. Groups 1-5 showed no significant effect in in body weights and testes weights of Swiss mice. Plasmodium berghei (malaria) and chloroquine have effects on histomorphological structures of Swiss mice testes but not on their teste’s weights. The testicular section from Swiss mice infected with malaria and treated at various doses when compared with the Control (Group 1) showed some moderate distortion in some structures like seminiferous tubules, connective tissues between the tubules, lumen and interstitial spaces. It can be deducted that Plasmodium berghei which caused parasitaemia in mice could cause a little tissue effect on mice if not treated.